- Literasi Keuangan dan Emosi terhadap Risk Perception Pengusaha Batik Tulis Lasem Rembang Jawa Tengah: - - Damayanti (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2022)
The purpose of this study was to analyze the factors that influence the risk perception of the batik entrepreneur Lasem Rembang. The factors studied include financial and emotional literacy. This study took the object of the Lasem batik SME in Rembang Regency, Central Java, Indonesia. The total population of the study was 102 Lasem Batik entrepreneurs, the sampling technique used saturated sampling. From the questionnaires that filled out there were 70 samples. Data collection techniques using a questionnaire. The results showed that 1). financial literacy has a significant positive effect on the risk perception of Lasem batik entrepreneurs, 2). Emotions have no significant negative effect on the risk perception of Lasem batik entrepreneurs, and 3). Financial literacy and emotion together have a positive and insignificant effect on the risk perception of Lasem batik entrepreneurs.